2009
DOI: 10.1002/jmri.21791
|View full text |Cite
|
Sign up to set email alerts
|

Settling properties of venous blood demonstrated in the peripheral vasculature using susceptibility‐weighted imaging (SWI)

Abstract: Purpose: To evaluate the settling properties of venous blood in the peripheral vasculature during periods of immobility. Materials and Methods:Susceptibility-weighted imaging (SWI) was performed for nine subjects at two time points: within 10 minutes of entering the magnet and after 40 minutes spent stationary in the magnet. Changes in the phase and in the distribution of phase of the veins were used to draw conclusions about the separation of red blood cells from plasma over time.Results: Settling was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…21 Such samples may paradoxically not cause a marked signal void in SWI either. This is in contrast with the findings of Barnes and associates 44 who have shown that in vivo blood sedimentation because of stasis in veins is related to phase shift and signal decrease in SWI.…”
Section: Discussioncontrasting
confidence: 99%
“…21 Such samples may paradoxically not cause a marked signal void in SWI either. This is in contrast with the findings of Barnes and associates 44 who have shown that in vivo blood sedimentation because of stasis in veins is related to phase shift and signal decrease in SWI.…”
Section: Discussioncontrasting
confidence: 99%
“…IPH is usually defined as a two‐fold hyperintense signal within the carotid wall compared with adjacent sternocleidomastoid muscle. Normal vessel walls and calcification are diamagnetic , whereas IPH is paramagnetic. This leads to opposite phase polarities, which could be utilized in SWI and QSM for better differentiation of calcification from IPH .…”
Section: Clinical Applications Of Swimentioning
confidence: 99%
“…Although this technique is in constant development, it has several clinical applications including the detection of trauma associated hemorrhages, strokes, brain tumors, neurodegenerative diseases and Sturge-Weber syndrome [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%